Wearing Veil in Indonesia Public Schools: Religious awareness or Political Contest - Muhaemin Latif (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
This article discusses the reason of wearing veil among Indonesian Students in public schools. It is found that that veil in public schools has three different elements. First of all, veil is identified as the religious awareness among the students. It symbolizes the religious commitment and the strength of local values. The proliferation of veiled women indicated the Islamic movement in Indonesia. Secondly, veil may be identified as the medium of maintaining political interest. The policy of making veil compulsory for students and as school uniform can ignore the pluralism in Indonesia. This policy also leads to make veil as a symbolic than substantive teaching. Finally, veil in public schools should be considered as the social control for the female students in the public sphere. It does not merely focus on the symbolic sphere but it extends to develop the achievement of students